Neoplastic and Nonneoplastic Cutaneous Tumors of Dogs in Grenada, West Indies. (25th December 2011) - Chikweto, A.; McNeil, P.; Bhaiyat, M. I.; Stone, D.; Sharma, R. N.
Abstract : This retrospective survey was undertaken between 2002 and 2007 on samples from dogs residing in Grenada. The objectives of the study were to identify the most common histologic types of canine cutaneous tumors, determine the relative frequency of each tumor type, and compare results to reports from other regions. In a series of 225 skin masses examined, the proportion of neoplasms was 72% whereas nonneoplastic tumors accounted for 15.6%, and inflammatory conditions constituted 12.4%. There were 10 types of nonneoplastic tumors with hamartomas being the most common (28.5%), followed by sebaceous hyperplasia (25.7%) and fibroepithelial polyps (22.8%). The 10 most common cutaneous neoplasms were hemangiosarcomas (19.1%), histiocytomas (8.6%), melanocytomas (8%), mast cell tumors (6.8%), lipomas (6.8%), hemangiopericytomas (6.2%), papillomas (5.6%), fibrosarcomas (5.6%), hemangiomas (4.9%), and squamous cell carcinomas (4.3%). Tumors of vascular origin and transmissible venereal tumors were more common in dogs in our study than reported from other regions.